Improving Transition Practices: Understanding Family Experiences and Needs in Transitioning Their Child to Developmental/Rehabilitation Services. (1st June 2016) - Ballantyne, M; Sozer, A; Orava, T; Bernardo, S; McPherson, A; Church, P; Fehlings, D; Cohen, E
Abstract: BACKGROUND: Children born preterm (<37 weeks) with cerebral palsy (CP) have long-term complex medical needs that require transitions between multiple healthcare services, necessitating parental support. The experiences of parents undergoing early transitions from the neonatal intensive care unit (NICU) to neonatal follow-up clinics (NFUC) to home are well-documented. Our prior research conducted found parents described positive transitions as: access to information, feeling involved in care and witnessing improvement in their child's health outcomes post-transition. Negative experiences entail: unanticipated differences between healthcare services, feeling separated from their child and having inadequate information. Unfortunately, the next transition from children with CP born preterm (<37 weeks) to developmental/rehabilitation services (DRS) is grossly under-studied and knowledge from well-studied healthcare transitions has yet to be applied to this population. OBJECTIVES: To identify and describe the experience and needs of parents of children with CP born preterm, as they transition from NFUC to DRS. Additionally, to make recommendations building upon characteristics of supportive/positive transition experiences to meet the emotional, informational, and instrumental needs of parents during transition to DRS. DESIGN/METHODS: A descriptive qualitative study was conducted recruiting English-speaking parents of children born preterm with CP that required NICU hospitalization, and DRS post CP diagnosis. Purposeful and maximum variation strategies were used to recruit a sample of 15 parents. To ensure rigor, sampling continued until data saturation was reached. Interviews were audio-recorded, transcribed verbatim, coded using NVivo 10 software and underwent thematic analysis. Data collection and analyses were performed concurrently, with themes from early interviews incorporated, collapsed and used to inform later interviews. RESULTS: A majority of participants were mothers, whose child had received DRS for the past one to 12 years. Preliminary themes iterated by parents' transition experiences included: Poor communication of diagnosis caused anxiety surrounding transition of care; a lack of timely access to appropriate care and resources negatively affected parents' experiences; continuity and consistency of healthcare providers improved families' perception of accessibility to care; and social support was desired throughout the transition period. CONCLUSION: The transition between NFUC and DRS for families with CP is significant, but lacks best practice research to advise care. Preliminary recommendations derived from data reveal the need to better support families earlier on in the transition process, beginning at the NFUC. Further research is required to identify best practices to strengthen communication, family involvement, continuity of care, and timely access to informational supports for parents.